2005
DOI: 10.1111/j.1523-1755.2005.09419.x
|View full text |Cite
|
Sign up to set email alerts
|

Experience with a program for prevention of chronic renal failure in India

Abstract: This model provides an effective method for prevention of chronic renal failure at the community level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
74
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 1 publication
2
74
1
Order By: Relevance
“…The total cost amounts to 25 cents per capita of the study population. [42] A main tool to control CKD is patient cooperation in the treatment of underlying disease. Unfortunately, there is a lack of awareness in patients and general population.…”
Section: Gender-specific Prevalence Of Ckdmentioning
confidence: 99%
“…The total cost amounts to 25 cents per capita of the study population. [42] A main tool to control CKD is patient cooperation in the treatment of underlying disease. Unfortunately, there is a lack of awareness in patients and general population.…”
Section: Gender-specific Prevalence Of Ckdmentioning
confidence: 99%
“…In countries where the living conditions are somewhat improving, and the income is increasing, a worrisome increase in CVD and diabetes is witnessed (34,35). In low-income countries, social and public health pilot experiences have shown that early detection of CKD is feasible at affordable costs (36,37). The next step is to provide aid to these countries and to also prove that inexpensive treatment for the prevention of CKD progression is possible.…”
Section: Figurementioning
confidence: 99%
“…With an incidence of 151-163 per million population, End Stage Renal Disease (ESRD) is definitely growing at a fast rate [1]. It is also known that hypertensive and diabetic patients are at a higher propensity to develop kidney diseases and these account for 29.8% and 4.8% of the Indian population respectively [2,3,4]. A significant portion of the population, therefore, is at a growing risk of developing CKD.…”
Section: Introductionmentioning
confidence: 99%